Depressão: resistência ou desistência existencial? - Hartmann Júnior, José Antônio Spencer (2006)
The present work make deeper of the depression, summon the existence questions of the individual and your world relation, how the possibility for the better to comprehend your psychic pain and yours report with the modern social. With inspiration in the existential phenomenologic approach, what help me too much in my depression reflection, - how the crise of life sense symptom to did realize a intersections with the social transit this individual how being-in the-world. The questions rise in to know how the man in actuality answer a the actuals ontics conditions of your exist marked for the social what bring mark well delineated in the work and what did nominated depressivist mechanism.The mode of affectation this individual for the contemporary psychological-social aspects it may be understanding how a answer for the mode how the world appear to him; may to characterize how a desistance manner when the depressed deny the life, negating yourself, condition at miscarriage sentiment, personal insufficience, guilt and frustration; or the resistance, when the depressed answer for the world how the protest act living in self- punishment. In despite of, this a sterile protest because paralyze the individual in front of another possibility in your exist. The work travelling about in the problematic of the depression what may be comprise how a resistance or desistance of live. At last, the work disembogue in the psychological clinic how a place where this individual may be change your life sense, at the same time, propose a reflection for the depression clinic in the actuality how much the importance at a existential phenomenologic approach this individual what insert in your analytical a look more accurate not other than individual ontological questions, but how this individual being-in the-world pass by historical-cultural-social in your subjectivation mode